2014
DOI: 10.1039/c4dt00022f
|View full text |Cite
|
Sign up to set email alerts
|

Gold complexes as antimicrobial agents: an overview of different biological activities in relation to the oxidation state of the gold ion and the ligand structure

Abstract: Interest in antimicrobial gold complexes originated from the work of Robert Koch at the end of 19th century, who demonstrated that potassium dicyanidoaurate(I), K[Au(CN)2], showed activity against Mycobacterium tuberculosis, a causative agent of tuberculosis. Subsequently, a large number of gold(I) and gold(III) complexes have been evaluated as possible antimicrobial agents against a broad spectrum of bacteria, fungi and parasites. The first part of the present review article summarizes the results achieved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(118 citation statements)
references
References 96 publications
1
108
0
Order By: Relevance
“…Thanks to their favorable and peculiar chemical and biological properties, gold(I) Nheterocyclic carbene compounds have been tested extensively in recent years as antiarthritic 15 , antibacterial 16 and anticancer agents 2,[11][12][13][14][18][19][20][21][22][23][24][25][26] .…”
Section: Reaction Between the Gold N-heterocyclic Carbene Compound Aumentioning
confidence: 99%
“…Thanks to their favorable and peculiar chemical and biological properties, gold(I) Nheterocyclic carbene compounds have been tested extensively in recent years as antiarthritic 15 , antibacterial 16 and anticancer agents 2,[11][12][13][14][18][19][20][21][22][23][24][25][26] .…”
Section: Reaction Between the Gold N-heterocyclic Carbene Compound Aumentioning
confidence: 99%
“…Reflecting the increasing interest in the antimicrobial activity of gold compounds, very recently, a comprehensive review of the developments in this field appeared [16]. While studies have been reported on phosphanegold(I) monofunctional thiolate compounds, none have yet appeared for bi-functional dithiolate analogues, such as dithiocarbamate.…”
Section: Introductionmentioning
confidence: 99%
“…The same dithiocarbamate ligands when complexed to bismuth(III) [17] and zinc(II) [18] also provide cytotoxic compounds. Over and above displaying interesting cytotoxicity profiles, phosphanegold(I) dithiocarbamates also display potential as anti-microbial agents; see [19] for a recent review on the utility of gold compounds in this context. Interestingly, for these R3PAu[S2CN(iPr)CH2CH2OH] compounds, activity was found to be dependent on the nature of the phosphanebound R substituent.…”
Section: Introductionmentioning
confidence: 99%